Analisis Pembiayaan Murabahah Pada Baitul Maal Wat Tamwil Dalam Proses Jual Beli Usaha Mikro, Kecil, Dan Menengah (Studi Kasus Pada Bmt Usaha Gabungan Terpadu Nusantara Capem Kencong): Analysis of Murabahah Financing at Baitul Maal Wat Tamwil in the Buying and Selling Process of Micro, Small, and Medium Enterprises (Case Study at BMT Usaha Gabon Terpadu Nusantara Capem Kencong) - Anggraini, Anggun Astri (IJABAH: Indonesian Journal of Sharia Economics, Business, and Halal Studies, 2024)
This research aims to determine the impact of implementing Murabahah financing in the buying and selling process for Micro, Small and Medium Enterprises (MSMEs) at BMT UGT Nusantara. This research uses a descriptive qualitative approach with the type of field research. The location that is the object of this research is BMT UGT Nusantara Capem Kencong. Researchers used primary data obtained through interviews, observation and documentation. Data validity analysis uses triangulation techniques. The results of the research conclude that Murabahah financing at BMT UGT Nusantara Capem Kencong has a good impact on the economy, especially on the surrounding MSMEs, which can be proven by several developments that have occurred in MSMEs through indicators including increasing income, increasing trading facilities (ruko), and increasing the number of buyer